Land use, hydrology, and climate influence water quality of China's largest river. (15th September 2022) - Xiong, Fangyuan; Chen, Yushun; Zhang, Shuanghu; Xu, Yanxue; Lu, Ying; Qu, Xiao; Gao, Wenqi; Wu, Xinghua; Xin, Wei; Gang, Daniel Dianchen; Lin, Lian-Shin
Abstract: Influences of multiple environmental factors on water quality patterns is less studied in large rivers. Landscape analysis, multiple statistical methods, and the water quality index (WQI) were used to detect water quality patterns and influencing factors in China's largest river, the Yangtze River. Compared with the dry season, the wet season had significantly higher total phosphorus (TP), chemical oxygen demand (COD), total suspended solids (TSS), and turbidity (TUR). The WQI indicated "Moderate" and "Good" water quality in the wet and dry seasons, respectively. Compared with other sites, the upper reach sites that immediately downstream of the Three Gorges Dam had lower TP, TN, TSS and TUR in both seasons, and had lower and higher water temperature in the wet and dry seasons, respectively. Water quality patterns were mainly driven by heterogeneity in land use (i.e., wetland, cropland, and urban land), hydrology (i.e., water flow, water level), and climate (i.e., rainfall, air temperature). Water quality in the wet season was primarily driven by land use while the joint effect of land use and hydrology primarily drove in the dry season. Decision-makers and regulators of large river basin management may need to develop programs that consider influences from both human and natural drivers for water quality conservation. Highlights: The WQI showed Moderate to Good water quality in China's largest river. Dam impoundment reduced nutrients and TSS downstream. Land use was the main driver for water quality in the wet season. Land use and hydrology jointly drove water quality in the dry season. Management may consider prioritizing the 5 km riparian zone for conservation.